2012
DOI: 10.1002/mrc.3879
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and complete 1 H and 13C assignment of some pentacyclo[5.4.0.02,6.03,10.05,9]undecane‐8,11‐dione (PCUD) derivatives

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Entry 6 describes the known3638 intramolecular cycloaddition of dieneone 12 to caged diketone 13 with a single 36 W UVA lamp in flow. The batch reaction was conducted by using approximately 50 % immersion of the lamp.…”
Section: Resultsmentioning
confidence: 99%
“…Entry 6 describes the known3638 intramolecular cycloaddition of dieneone 12 to caged diketone 13 with a single 36 W UVA lamp in flow. The batch reaction was conducted by using approximately 50 % immersion of the lamp.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, HMBC, NOESY, and ROESY techniques are useful in determining the side "arm" with respect to the cage moiety. 48 Kenwright et al, 40 reported a series of compounds, 10a-10g (Figure 3), where the protons in the 2 and 6 positions of the four-membered ring have the highest shift in frequency of all the methine protons in unsubstituted PCU derivatives. However, the chemical shift of position 2 appears de-shielded when position 1 is substituted by an alkyl or methoxy group.…”
Section: Pentacycloundecanementioning
confidence: 99%